NEGOSIASI KULTURAL DALAM UPAYA ISLAMISASI TRADISI ROKAT MASYARAKAT MADURA PROBOLINGGO - Bulgis, Faizah Malikal; Rosa, Dien Vidia (Research Institute and Community Engagement of UIN MADURA, 2024)
In contemporary situations, the issue of the ancentral rokat tradition is closely associated with Islam. Nonetheless, in several literatures, reseachers typically concentrate on the history and rokat processes. Madura community in Tamansari Village, Probolinggo Regency, has a different history and meaning. Therefore, it is essential to examine the actions taken by the actors and the meanings that emerge in the community regarding changes in rokat tradition practice. This paper aims to examine the interpretation of the community and conduct a deeper analysis of the cultural negotiation process of the rokat tradition in the context of Islamization as a ritual practice. The research is conducted using a qualitative ethnographic research method, which includes direct observation, interviews, documentation, and a literature review, implementing the perspective of Mark R. Woodward. The research results indicate the existence of two categories of rokat leaders, namely the traditional Javanese rokat leader (adhering to ancestral teachings) and the Islamic rokat leader. The negotiation of Islamic rokat emerges through Islamic leaders who reinterpret the meaning of rokat within the framework of Islamic values, Meanwhile, Javanese rokat maintains the practice and traditional meaning. Islamic rokat is more preferred due to its relatively lower cost compared to Javanese rokat. However, some communities still firmly adhere to and believe in their traditional ancestral teachings, considering them as the refinement of tradition rather than just symbols.